Reactive Disruption of the Hippocampal Neurogenic Niche After Induction of Seizures by Injection of Kainic Acid in the Amygdala - Muro-García, Teresa; Martín-Suárez, Soraya; Espinosa, Nelson; Valcárcel-Martín, Roberto; Marinas, Ainhoa; Zaldumbide, Laura; Galbarriatu, Lara; Sierra, Amanda; Fuentealba, Pablo; Encinas, Juan Manuel (Frontiers in Cell and Developmental Biology, 2019)
Adult neurogenesis persists in the adult hippocampus due to the presence of multipotent neural stem cells (NSCs). Hippocampal neurogenesis is involved in a range of cognitive functions and is tightly regulated by neuronal activity. NSCs respond promptly to physiological and pathological stimuli altering their neurogenic and gliogenic potential. In a mouse model of mesial temporal lobe epilepsy (MTLE), seizures triggered by the intrahippocampal injection of the glutamate receptor agonist kainic acid (KA) induce NSCs to convert into reactive NSCs (React-NSCs) which stop producing new neurons and ultimately generate reactive astrocytes thus contributing to the development of hippocampal sclerosis and abolishing neurogenesis. We herein show how seizures triggered by the injection of KA in the amygdala, an alternative model of MTLE which allows parallel experimental manipulation in the dentate gyrus, also trigger the induction of React-NSCs and provoke the disruption of the neurogenic niche resulting in impaired neurogenesis. These results highlight the sensitivity of NSCs to the surrounding neuronal circuit activity and demonstrate that the induction of React-NSCs and the disruption of the neurogenic niche are not due to the direct effect of KA in the hippocampus. These results also suggest that neurogenesis might be lost in the hippocampus of patients with MTLE. Indeed we provide results from human MTLE samples absence of cell proliferation, of neural stem cell-like cells and of neurogenesis.